2003
DOI: 10.1002/jez.a.10312
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Gated ion currents of schwann cells in cell culture models of human neurofibromatosis

Abstract: K(+) (K) channels play a role in the proliferation of many cell types in normal cells and certain disease states. Several laboratories have studied K currents in cultured Schwann cells from models of the human diseases, neurofibromatosis type 1 (NF1) and neurofibromatosis type 2 (NF2). These diseases are characterized by the growth of Schwann cell tumors. In all cell culture NF models the K current properties differ in tumor-derived and normal Schwann cells. Depending on the model however, the type of K channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Expression of ion channels involved in regulation of cell proliferation is abnormal in neoplastic Schwann cells. 38 Schwann cells from tumor cell lines display abnormal cell-surface ligands implicated in cell migration, cell-matrix interaction, and tumor progression such as CD44. 39 Because we have used cells harvested directly from rat peripheral nerves, our study may more accurately reflect the effects of LAs on normal nerves in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ion channels involved in regulation of cell proliferation is abnormal in neoplastic Schwann cells. 38 Schwann cells from tumor cell lines display abnormal cell-surface ligands implicated in cell migration, cell-matrix interaction, and tumor progression such as CD44. 39 Because we have used cells harvested directly from rat peripheral nerves, our study may more accurately reflect the effects of LAs on normal nerves in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although whole cell voltage clamp analysis on neurofibromin deficient Schwann cells has demonstrated alterations in potassium currents [1012], to date there have been no studies addressing if ion channel activity is altered in neurons from Nf1 +/− mice. Our study addressed this gap in knowledge by measuring calcium currents from hippocampal neurons of wild-type and Nf1 +/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there have been no studies addressing if calcium channel activity is altered in neurons from neurofibromin deficient mice. Using whole cell voltage clamp analysis, it was shown that potassium currents are altered in neurofibromin deficient Schwann cells [1012], and a recent study demonstrated augmented sodium currents in sensory neurons from Nf1 +/− mice [13]. Here, we examined the complement of calcium channels underlying transmitter release in hippocampal neurons from wildtype and Nf1 +/− mice.…”
Section: Introductionmentioning
confidence: 99%